AN ANALYSIS OF STUDENTS’ PROBLEMS IN WRITING PASSIVE VOICE MADE BY THE SECOND GRADE OF SMAN 9 TAKALAR - Juliana Basir; Saiful; Firman (FKIP Unismuh Makassar, 2021)
The purpose of this research is to find out and analysis the students’ problems in writing passive voice made by the second grade of SMAN 9 Takalar. The design of this research was descriptive quantitative research. The total number of the sample was 15 students. The researcher used the purposive sampling technique. The instrument used to get the data was a test and questionnaire with Google Form as data collection tool. Based on the result, the researcher found the percentage of students’ problems in writing passive voice. The researcher found that 13 students with a percentage of 86,67% had a problem writing passive voice in the simple present tense, and 12 students with a percentage of 80,00% had a problem writing passive voice in the simple past tense. The causes that become problems for students in writing passive voice are knowledge and understanding, less practice, and educational background. Finally, based on the findings, it can be concluded that students of the second grade of SMA Negeri 9 Takalar have problems in writing passive voice and three causes that make students problems in writing passive voice.